Quantum Physics, Alternative Medicine, and Spirituality (Global Journal of Medical Research, 2019)
This article explains how quantum physics connects to alternative medicine and spirituality. These three things that seem so distant are connected through the human nonlinear electromagnetic field (NEMF), which only some sensitive individuals can see -it is called aura. However, aura could be made visible to everybody and to be photographed if high frequency electric field is used, which multiply the photons of our aura (NEMF) and makes its photographing possible. It is called Kirlian photography and it could make visible the discrete (quantum) energy levels of our NEMF. Since, the almost invisible NEMF is called Spirit, the quantum energy levels of our NEMF are de facto our quantum spiritual levels. How this relates to Alternative Medicine? The higher is the Spiritual level of an individual, the higher is the frequency of his NEMF and the higher is his sensitivity -emotional sensitivity, stress sensitivity, and drug sensitivity. If so, the right medicine for these more spiritual and more sensitive individuals would be the more gentle alternative medicine (homeopathy, herbal, or acupuncture). If western medicine is used on these sensitive individuals, the dose must be decreased a few times because what is the normal dose for the individuals with low sensitivity will be too much for them. They would suffer a bouquet of allergic reactions and the drugs would more harm than help them.
Keywords: quantum physics; quantum spiritual levels; our quantum computer; alternative medicine for sensitive (spiritual); spirituality